Multi-layer coatings designed for optical power enhancement of long-wavelength infrared quantum cascade lasers - Niewczas, Dominika; Krząstek, Agata; Pierścińska, Dorota; Stefaniuk, Tomasz; Broda, Artur; Pierściński, Kamil (Optics letters, 2025)
In this study, we present the design, fabrication, and experimental validation of two types of multilayer optical coatings aimed at enhancing the performance of long-wavelength infrared (LWIR) quantum cascade lasers (QCLs). A high-reflectivity (HR) coating was developed using a three-layer structure (200 nm /10 nm /100 nm ), while a novel partial-reflectivity (PR) coating was realized with a double-layer design (360 nm /120 nm ). The optical constants of the constituent materials were determined by spectral ellipsometry and used in numerical simulations to optimize the coatings' performance. To verify the optical response of the fabricated coatings, FTIR reflectivity measurements were carried out directly on the deposited structures. The experimental results showed excellent agreement with simulations, confirming high optical quality. The optimized HR and PR coatings were subsequently applied to the back and front facets, respectively, of QCLs operating at a wavelength of 9.3 µm. Light-current-voltage (LIV) measurements demonstrated a significant increase in optical output power-from 974 mW to 1653 mW per facet-only when both coatings were simultaneously implemented, with the threshold current density remaining unchanged. Reflectivity values derived from LIV characteristics confirmed 96% reflectance for the HR coating and 9% for the PR coating. This work presents the first, to the best of our knowledge, implementation of a Y O /Ge-based two-layer PR coating directly deposited on QCL facets, which enabled a significant increase in the optical power of lasers.